A new sample treatment strategy based on simultaneous supramolecular solvent and dispersive solid-phase extraction for the determination of ionophore coccidiostats in all legislated foodstuffs. (1st October 2020) - González-Rubio, S.; García-Gómez, D.; Ballesteros-Gómez, A.; Rubio, S.
Highlights: Supramolecular solvents and dispersive SPE are firstly combined for sample treatment. The approach is tested in the determination of ionophore coccidiostats in foodstuff. SUPRAS removes proteins and carbohydrates and dSPE fats and other organic compounds. Single-step sample treatment with no further clean-up or evaporation steps required. Fully validated LC-MS/MS method for determining ionophores in all legislated foods. Abstract: A single-step sample treatment, for the simultaneous extraction and clean-up for the determination of ionophore coccidiostats in EU legislated foodstuffs, is here proposed. The treatment is based on the combination of: (i) a supramolecular solvent with restricted access properties (SUPRAS-RAM), spontaneously formed by the addition of hexanol, water and THF to the sample; and (ii) dispersive solid phase extraction (dSPE). The SUPRAS-RAM extract was directly compatible with LC-MS/MS and no further re-extraction, evaporation or cleanup procedures were necessary. SUPRAS-RAM efficiently extracted the ionophores (recoveries in milk, eggs, fat, liver, kidney, and chicken and beef muscle were in the range 71–112%) and removed proteins and carbohydrates, whereas dSPE removed fats and other lipophilic compounds. The method was validated following the European Commission Decision 2002/657/EC. Detection limits (0.004–0.07 µg kg −1 ) were far below the maximum residue limits (1–150 µg kg −1 ). Method analytical and operational characteristics were suitable for routine determination of ionophores.